Higher HbA1c levels associate with lower hippocampal serotonin transporter availability in non-diabetic adults with obesity - Grundmann, Rico (Sci Rep, 2020)
The current study aimed to investigate whether the in vivo availability of central serotonin reuptake transporters (5-HTT) is associated with plasma levels of glycosylated hemoglobin (HbA1c) in non-diabetic humans with obesity. 5-HTT availability was measured by using positron emission tomography (PET) imaging with the 5-HTT selective radiotracer [(11)C]DASB in 23 non-diabetic individuals with obesity and 14 healthy, non-obesity controls. Parametric images of binding potential BP(ND) were generated from the PET data and analyzed together with HbA1c levels by using volume of interest analysis for brain areas relevant to appetite control. Voxel-based morphometry (VBM) of individual magnetic resonance imaging data was further performed to correlate grey matter density (GMD) maps with HbA1c. We found significant negative correlations between HbA1c levels and BP(ND) in right and left hippocampus in obesity (r = − 0.717, p < 0.001, and r = − 0.557, p = 0.006, respectively). VBM analyses revealed that higher HbA1c levels were associated with GMD in the right para-hippocampal area. Our results indicate that chronically high blood glucose levels may evoke changes in hippocampal 5-HTT levels that are in part tied to local microstructure.